Extent of automation and the readiness for Industry 4.0 among Malaysian furniture manufacturers - Ratnasingam, J.; Ab Latib, H.; Yi, L.; Liat, L.; Khoo, A. (College of Natural Resources, North Carolina State University, 2019)
Automation offers a promising solution to improve competitiveness for the labor-intensive furniture manufacturing sector in Malaysia. This study evaluated the level of application of automation, the factors driving it, and the readiness of the furniture manufacturers towards Industry 4.0. A questionnaire-based survey was targeted to large and medium-sized furniture manufacturers throughout Malaysia, with responses from 312 manufacturers. The results revealed that the panel-based furniture manufacturers were more responsive towards the adoption of automated technologies than other types of furniture manufacturers. The machining centers and finishing operations within the furniture factories showed the highest application of automated technologies. The factor analysis revealed that the drivers for the application of automated technologies were the desire for higher production capacity, cost involved, product characteristics, and government policy. This study emphasized that in the cost-sensitive furniture manufacturing industry, the economic benefits of applying automation outweigh any other factor in the decision to explore such technologies. The study also revealed that furniture manufacturers are not ready to adopt Industry 4.0, and any efforts by the government to push for such transformation will require the provision of incentives and other tangible economic benefits.